SnO2@N‐Doped Carbon Hollow Nanoclusters for Advanced Lithium‐Ion Battery Anodes (Eur. J. Inorg. Chem. 6/2016). Issue 6 (February 2016) - Li, Lu; Zhang, Lingyu; Chai, Fang; Wang, Tingting; Li, Zilu; Xie, Haiming; Wang, Chungang; Su, Zhongmin
Abstract : The cover picture shows a unique functional nanoarchitecture, monodisperse SnO2 @N‐doped carbon hollow nanoclusters. The uniqueness of this structure is due not only to the large amount of ultrafine small SnO2 nanoparticles it contains, but also to the interior space, as well as the continuous N‐doped carbon shells, which efficiently buffer huge changes in volume and guarantee the electrical connectivity. All these features make the nanocomposite well‐suited for lithium storage and significantly improve the electrochemical performance of lithium‐ion batteries. Details are discussed in the article by F. Chai, C. Wang, Z. Su et al. onp. 812 ff . For more on the story behind the cover research, see theCover Profile .